2016
DOI: 10.1016/j.diii.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Applications of dual energy computed tomography in abdominal imaging

Abstract: Dual energy computed tomography (CT) is an imaging technique based on data acquisition at two different energy settings. Recent advances in CT have allowed data acquisition and almost simultaneously analysis of two spectra of X-rays at different energy levels resulting in novel developments in the field of abdominal imaging. This technique is widely used in cardiovascular imaging, especially for pulmonary embolism work-up but is now also increasingly developed in the field of abdominal imaging. With dual-energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Although the past study reported that the iodine map improved the detection of these lesions in the pancreatic cancer, it could not eliminate the bone region. 8 In the current study, we investigated the correlation between the rED and CT number, and we created the contrast medium extraction method using rED using sinogram data and CT number from DECT. Figure 1 shows the two phantoms used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the past study reported that the iodine map improved the detection of these lesions in the pancreatic cancer, it could not eliminate the bone region. 8 In the current study, we investigated the correlation between the rED and CT number, and we created the contrast medium extraction method using rED using sinogram data and CT number from DECT. Figure 1 shows the two phantoms used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dual-energy CT imaging has become available to reduce the beam hardening effect contributing to the artifacts caused by the contrast agent [1113]. Approaches such as image acquisition with different beam energy or using energy-resolved photon-counting detectors are used to perform the dual-energy CT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine mapping is among the most frequently reported clinical applications of dual energy computed tomography (DECT) [ 1 6 ]. Iodine maps display the local concentration of iodine from iodinated contrast agent, and can serve as an indicator of local perfusion.…”
Section: Introductionmentioning
confidence: 99%